2020
DOI: 10.21608/jppp.2020.114586
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Potassium Fertilization Levels on The Population Density of The Leafhopper and Planthopper Species Attacking Eggplant in Gharbia Governorate تأثیر مستویات التسمید البوتاسی علی الکثافة العددیة نطاطات الأوراق ونطاطات النباتات التی تهاجم محصول الباذنجان فی محافظة الغربیة

Abstract: The present experiment was conducted in Zefta, Gharbia governorate to examine the influence of fertilization levels on the population density of the different leafhoppers and planthoppers attacking eggplant crop during the two successive seasons (2017and 2018). The potassium fertilization levels of zero kg/fed. to 25, 50, and 75 kg/fed. attracted the highest average number of the leafhopper and planthopper species during the two seasons. The present study indicated that increasing potassium fertilization rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…The statistical analysis revealed that there were significant differences in the incidence of pest in the different levels of potassium fertilization during 2018 and 2019. These results agree with earlier ones (Youseef, 2006;Al-Habashy, 2008;Mansour, 2017) on wheat;Hasham et al (2009) on broccoli; Abou-Zaid (2011) on kidney-bean, and Awadalla et al (2020) on eggplant. The high level of K fertilizer minimizes the magnitude of accumulated amino acids that in turn can reduce the population of sucking insects (Jansson and Ekbom, 2002).…”
Section: Resultssupporting
confidence: 92%
“…The statistical analysis revealed that there were significant differences in the incidence of pest in the different levels of potassium fertilization during 2018 and 2019. These results agree with earlier ones (Youseef, 2006;Al-Habashy, 2008;Mansour, 2017) on wheat;Hasham et al (2009) on broccoli; Abou-Zaid (2011) on kidney-bean, and Awadalla et al (2020) on eggplant. The high level of K fertilizer minimizes the magnitude of accumulated amino acids that in turn can reduce the population of sucking insects (Jansson and Ekbom, 2002).…”
Section: Resultssupporting
confidence: 92%